2023
DOI: 10.1128/spectrum.00268-23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Rapid Multiplex Gastrointestinal Panel with Standard Laboratory Testing in the Management of Children with Hematochezia in a Pediatric Emergency Department: Randomized Controlled Trial

Abstract: Advances in diagnostic microbiology now allow for the faster and more accurate detection of an increasing number of pathogens. We determined, however, that in children with acute bloody diarrhea, these advances did not necessarily translate into improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Prior studies of bloody diarrhea in children, before the widespread availability of multiplex PCR, had been limited to conventional stool culture, immunoassays, and a limited array of PCR detection methods [5,7,8]. Our findings align with more contemporary multiplex PCR-based studies of either bloody diarrhea, or more generally hematochezia, emphasizing the complexity of attributing bloody diarrhea symptoms to specific pathogens [4].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Prior studies of bloody diarrhea in children, before the widespread availability of multiplex PCR, had been limited to conventional stool culture, immunoassays, and a limited array of PCR detection methods [5,7,8]. Our findings align with more contemporary multiplex PCR-based studies of either bloody diarrhea, or more generally hematochezia, emphasizing the complexity of attributing bloody diarrhea symptoms to specific pathogens [4].…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis of data from a multi-site study revealed that in less than half of the cases with bloody diarrhea was a bacterial pathogen typically associated with this condition detected, and that in a substantial proportion (over a third) of bloody diarrhea cases, a pathogen was detected for which antibiotics was not indicated. Prior studies of bloody diarrhea in children, before the widespread availability of multiplex PCR, had been limited to conventional stool culture, immunoassays, and a limited array of PCR detection methods[5,7,8]. Our findings align with more contemporary multiplex PCR-based studies of either bloody diarrhea, or more generally hematochezia, emphasizing the complexity of attributing bloody diarrhea symptoms to specific pathogens[4].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations